Identification of Urban Heat Island (UHI) in the City of Padang from 2019-2023 using Multitemporal Images Case Study: Padang City Area, West Sumatra - Mentari Dian Pertiwi; Sri Kandi Putri; Nabilla Afifah; Wilda Islamisari (Sustainability (STPP) Theory, Practice and Policy, 2024)
The increase in population and urban development leads to higher energy consumption, which adversely affects environmental quality. The resulting impacts include a reduction in green open spaces, an increase in air pollution, and a rise in surface temperatures. This leads to the phenomenon known as the Urban Heat Island (UHI), where urban areas experience higher temperatures than their rural surroundings. This research aims to identify the UHI in Padang City using Landsat multitemporal data over a 5-year observation period from 2019 to 2023. The method involves converting digital numbers from Landsat 8 OLI/TIRS and Landsat 9 satellite images in the Thermal Band to generate Land Surface Temperature (LST) data. Subsequent processing is carried out in GIS software, such as QGIS or ArcGIS, to obtain the distribution of UHI. The research findings indicate fluctuations in land surface temperatures, with both increases and decreases observed over the study period. Each year witnesses an expansion of the UHI area, indicating worsening heat conditions in various regions of Padang City. The findings suggest that land surface temperatures will continue to rise with further urban expansion, highlighting the need for proactive measures. Therefore, it is crucial to develop and implement policies to control and mitigate the negative impacts of UHI in urban spatial planning.